2022
DOI: 10.2196/33681
|View full text |Cite
|
Sign up to set email alerts
|

Technology Acceptance and Usability of a Virtual Reality Intervention for Military Members and Veterans With Posttraumatic Stress Disorder: Mixed Methods Unified Theory of Acceptance and Use of Technology Study

Abstract: Background Military members and veterans exhibit higher rates of injuries and illnesses such as posttraumatic stress disorder (PTSD) because of their increased exposure to combat and other traumatic scenarios. Novel treatments for PTSD are beginning to emerge and increasingly leverage advances in gaming and other technologies, such as virtual reality. Without assessing the degree of technology acceptance and perception of usability to the end users, including the military members, veterans, and the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…As part of an investigation into the feasibility to provide a complementary inpatient strategy for patient-controlled access to distraction, information, resources, and support to promote wellbeing during complex care, this study demonstrated the safety, acceptance, and potential utility of readily available VR technology for patients, their supporters, and staff. Our ndings in haematooncology patients is supported in other patient groups [24] but experience in prolonged inpatient complex care is limited. [2] Virtual reality has been applied in the management of mental health conditions, coaching, rehabilitation, pain management, health education, procedure and process familiarisation with some promising results.…”
Section: Discussionmentioning
confidence: 91%
“…As part of an investigation into the feasibility to provide a complementary inpatient strategy for patient-controlled access to distraction, information, resources, and support to promote wellbeing during complex care, this study demonstrated the safety, acceptance, and potential utility of readily available VR technology for patients, their supporters, and staff. Our ndings in haematooncology patients is supported in other patient groups [24] but experience in prolonged inpatient complex care is limited. [2] Virtual reality has been applied in the management of mental health conditions, coaching, rehabilitation, pain management, health education, procedure and process familiarisation with some promising results.…”
Section: Discussionmentioning
confidence: 91%
“…Evidence from a recent systematic review suggests that personalised, co-created, virtual reality exposure therapies for veterans with PTSD are beneficial [ 38 ]. Evidence also exists that the technology associated, specifically, with 3MDR is acceptable to patients and therapists [ 39 ] Consensus work has also commenced to specify the hardware and software necessary for 3MDR [ 40 ]. In addition to these ‘technical’ aspects of therapy and the clinic environment as part of the ‘intervention’ domain, our data support the idea that the relationship between therapist and patient remains important.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the proposed acceptance model, we will test the multivariate research model using the partial least squares structural equation modelling (PLS), which estimates complex cause-effect relationships in path models with latent variables (Jones et al 36 2022). The PLS measurement model will be evaluated by measuring: (1) the reliability of each construct (Cronbach’s alpha); (2) the convergent validity of each set of items with respect to their associated construct, by examining the factor loadings of the items on the model’s constructs and (3) discriminant validity with the AVE (Average Variance Extracted) indicator.…”
Section: Methods and Analysismentioning
confidence: 99%